The Role of Village Government in Community Empowerment in Tuyau Village, Pematang Karau Subdistrict, East Barito Regency - Muhammad Afriaji; Erwin Maulana; Selamat Riadi (Research Parks Publishers, 2025)
The role of the village government is a very important factor in increasing community empowerment. In Tuyau village, the village government in community empowerment is still not maximal in carrying out its role. The lack of the role of the village government in providing facilities and services, the lack of role of the village government in mobilizing the community by rarely providing community personal building activities, and the lack of the role of the village government in providing support in the form of special empowerment policies so that activities can run as expected. Based on the above, this study aims to determine the role of village government in community empowerment, determine the factors that influence the role of village government in community empowerment and the efforts made to overcome the factors that influence the role of village government in community empowerment in Tuyau Village, District Pematang Karau, East Barito Regency. This research uses a qualitative approach with a descriptive-qualitative type. Data collection techniques used are interviews, observation and documentation. Sources of data were taken through purposive sampling of 13 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation, and verification or drawing conclusions. The results of the study show that the role of village government in community empowerment in Tuyau village has not been fully implemented. The role of village government that has been running well can be seen from increasing productivity, increasing competence, providing facilities and infrastructure and providing technical skills. The aspects that are not good are policy makers, overcoming problems, increasing participatory empowerment, agents accelerating change, education and training providers, as well as counseling and mentoring providers. The inhibiting factors that affect empowerment are the lack of openness of the village government, the infrequent socialization or counseling related to empowerment and the occurrence of delays in program implementation. The supporting factors that influence are the annual routine training or courses and the provision of supplies to improve community businesses. To increase the role of the village government in empowering the community in Tuyau Village, it is hoped that the village head will be more open to the community, both from designing policies and making programs. The village officials are expected to be able to understand and be aware of their functions, roles and authorities as community service providers and the community is expected to have an open mind, try to participate in every empowerment program organized by the village government.